Efisiensi Penggunaan Potret Udara Non-Metrik Format Kecil dengan Tehnik Pengambilan Contoh Berganda - I Nengah Surati Jaya; Agung Budi Cahyono (Institut Pertanian Bogor (IPB University), 2001)
A comparison study on the efliciency of the use of smaN format non-metric aerial photographs(SFNAP) and conventional (metric) aerial photographs (CAP) was performed. The relative efficiency was computed based upon the implementation of double sampling with regression technique in comparison with the use of simple random sampling. The study found that, for estimating stand volume of teak wood, the SFNAP provided better sampling error as well as relative efficiency than those provided by the CAP. The relative efficiency of the SFNAP is 296.7% while therelative efficiency of the CAP is 225.7%. Economically this study expressed that, the use of the SFNAP for forest inventory using double sampling technique is cheaper than using the CAP.